2006
DOI: 10.1149/1.2164724
|View full text |Cite
|
Sign up to set email alerts
|

Speciation Analysis of Au(I) Electroplating Baths Containing Sulfite and Thiosulfate

Abstract: An analysis of the speciation of gold plating solutions containing sulfite and thiosulfate as complexing agents has been performed. In the case of gold sulfite baths, it was found that the observed stability and electrochemical behavior were inconsistent with the commonly assumed stability constants of ␤ = 10 10 for the Au͑SO 3 ͒ 2 3− species. The data are, however, consistent with a much larger stability constant of ␤ = 10 27 . In gold plating baths containing sulfite and thiosulfate ligands, the speciation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 32 publications
2
59
0
Order By: Relevance
“…The existence of the mixed ion complex was suggested in previous studies based on the deposition potential. It was also reported that the results from the sulfide-only bath are consistent with a higher stability constant (10 27 ), rather than the commonly assumed value of 10 10 [49].…”
Section: Noncyanide Bathsmentioning
confidence: 92%
“…The existence of the mixed ion complex was suggested in previous studies based on the deposition potential. It was also reported that the results from the sulfide-only bath are consistent with a higher stability constant (10 27 ), rather than the commonly assumed value of 10 10 [49].…”
Section: Noncyanide Bathsmentioning
confidence: 92%
“…Generally, the pH value of solution affects the co-deposition behavior frequently by altering the form of complexes. It was reported that the dominant electro-active in the gold sulfite bath species was the [Au(SO 3 ) 2 ] 3-complex with the pH value ranging from 2 to 12 [18][19][20] 3 -and Sn 2 (OH) 2 2? , formed in the developed alkaline electrolyte [21,22].…”
Section: Methodsmentioning
confidence: 99%
“…1 Now, the beginning of the reduction changes to approximately -600 mV Ag/AgCl , possibly due to a different surface conditioning promoted by sulfite. Also, it is observed a cathodic peak, indicated by a dashed arrow at -950 mV Ag/AgCl .…”
Section: Voltammetry Measurementsmentioning
confidence: 99%
“…1 Non-cyanide baths have been developed to overcome the problem of toxicity, most of them based on Au(I)-sulfite complex. 2,[3][4][5][6][7] Different reducing agents are commonly add to the Au(I)-sulfite bath, as thiourea, 5,6 hypophosphite, 4,6 borohydride, 6 dimethylamine borane (DMAB), 6 hydrazine 6 and formaldehyde.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation